Role of NAD(P)H:Quinone Oxidoreductase 1 in Clofibrate-Mediated Hepatoprotection from Acetaminophen - Moffit, Jeffrey S (2006)
Mice pretreated with the peroxisome proliferator clofibrate (CFB) are resistant to acetaminophen (APAP) hepatotoxicity. Whereas the mechanism of protection is not entirely known, CFB decreases protein adducts formed by the reactive metabolite of APAP, N-acetyl-p-benzoquinone imine (NAPQI). NAD(P)H:quinone oxidoreductase 1 (NQO1) is an enzyme with antioxidant properties that is responsible for the reduction of cellular quinones. We hypothesized that CFB increases NQO1 activity, which in turn enhances the conversion of NAPQI back to the parent APAP. This could explain the decreases in APAP covalent binding and glutathione depletion produced by CFB without affecting APAP bioactivation to NAPQI. Administration of CFB (500 mg/kg, i.p.) to male CD-1 mice for 5 or 10 days increased NQO1 protein and activity levels. To evaluate the capacity of NQO1 to reduce NAPQI back to APAP, we utilized a microsomal activating system. Cytochrome P450 enzymes present in microsomes bioactivate APAP to NAPQI, which binds the electrophile trapping agent, N-acetyl cysteine (NAC). We analyzed the formation of APAP-NAC metabolite in the presence of human recombinant NQO1. Results indicate that NQO1 is capable of reducing NAPQI. The capacity of NQO1 to amelioriate APAP toxicity was then evaluated in primary hepatocytes. Primary hepatocytes isolated from mice dosed with CFB are resistant to APAP toxicity. These hepatocytes were also exposed to ES936, a high affinity, irreversible inhibitor of NQO1 in the presence of APAP. Concentrations of ES936 that resulted in over 94% inhibition of NQO1 activity did not increase the susceptibility of hepatocytes from CFB treated mice to APAP. Whereas NQO1 is mechanistically capable of reducing NAPQI, CFB-mediated hepatoprotection does not appear to be dependent upon enhanced expression of NQO1.